2013
DOI: 10.1002/jms.3249
|View full text |Cite
|
Sign up to set email alerts
|

Novel and cost‐effective 6‐plex isobaric tagging reagent, DiART, is effective for identification and relative quantification of complex protein mixtures using PQD fragmentation

Abstract: Deuterium isobaric Amine Reactive Tag (DiART) reagents facilitate relative quantification during proteomic analysis in a functionally similar manner to commercially available isobaric tag for relative and absolute quantitation (iTRAQ) and tandem mass tag (TMT) reagents. In contrast to iTRAQ and TMT, DiART reagents incorporate deuterium isotopes which significantly reduce the number of required synthesis steps and hence have potential to significantly reduce reagent production cost. We examined the capability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…86 The analysis was performed by splitting each aorta extraction sample into three different analyses. The analyses were split to provide increased metabolic coverage using untargeted unlabeled analysis as well as isotopic labels for amine (DiART [87][88][89][90] ) and carbonyl (CILAT 91,92 ) analysis. All three sample regimes were separated using the same nLC column by simply changing separation conditions.…”
Section: Metabolomicsmentioning
confidence: 99%
“…86 The analysis was performed by splitting each aorta extraction sample into three different analyses. The analyses were split to provide increased metabolic coverage using untargeted unlabeled analysis as well as isotopic labels for amine (DiART [87][88][89][90] ) and carbonyl (CILAT 91,92 ) analysis. All three sample regimes were separated using the same nLC column by simply changing separation conditions.…”
Section: Metabolomicsmentioning
confidence: 99%
“…By using a similar technical approach, secretome alteration of industrially relevant lignocellulose degrading fungi, such as Aspergillus niger wild type and mutant strains [ 46 ], Phanerochaete chrysosporium [ 91 , 92 ] and Trichoderma reesei [ 47 , 93 ], were dug into deeply, detecting a number of biotechnologically significant enzymes. Finally, a novel isobaric tag, named deuterium ((2)H) isobaric amine-reactive tag (DiART) [ 94 ], has been introduced for quantitative proteomics and used to study Aspergillus nidulans cell wall proteins [ 95 ].…”
Section: Fungal Proteomicsmentioning
confidence: 99%
“…[111,117] In a study comparing DiART and iTRAQ, the authors found that DiART leads to more intense reporter ions and consequently less ratio compression, however with the DiART approach, the common fragmentation method is not advisable due to easy reporter ion fragmentation [118]. DiART has also proven to be compatible and valuable for PTM analysis as quantitative phosphoproteomic studies [119].…”
Section: Chemical Labeling Approaches: Isobaric Techniquesmentioning
confidence: 99%